The annual regional database of the European Commission (ARDECO): Methodological note - Davide Auteri; Carmelo Attardo; Matteo Berzi; Chiara Dorati; Federico Albinola; Lara Baggio; Giuseppe Bucciarelli; Ioris Bussolari; Lewis Dijkstra (European Commission, Joint Research Centre (JRC), 2024)
Quantitative indicators at the local level play an increasingly important role in the formulation and evaluation of regional policies. Regional statistical indicators are available from several sources, but comparability of their time-series is often affected by breaks caused by boundary changes (split or merge of regions) that modify the shape of the concerned areas over time. ARDECO (Annual Regional Database of the European Commission) aims to offer full comparability of long and harmonised time-series of demographic and socio-economic variables at the regional and sub-regional level. ARDECO is released on a quarterly basis, with two major releases in correspondence of the public availability of the AMECO Spring (May) and Autumn (November) economic forecasts. The two major releases are complemented by a release in March, which includes the annual update of regional accounts from Eurostat, and by an interim release during the summer. In case of need, minor versions are also released at other times of the year.
Keywords: 330; Regional development; Economic data; Database; EU states; Regionalentwicklung; Wirtschaftsdaten; Datenbank; EU-Staaten